Bilevel optimization of a distribution of interbudget transfers within given limitations - Semenov, V.V. (Reports of the National Academy of Sciences of Ukraine, 2019)
The problems of optimal distributing of transfers are defined and investigated within given budget limitations with the purpose of maximization of the social welfare in accordance with predefined criteria. The mathematical model is presented as a bilevel optimization problem, containing a linear problem of integer optimization at the bottom level, whose optimal solution is used for setting a feasible region of a bilevel problem. The optimistic and pessimistic problem definitions on the optimal distributing of transfers are considered. For the approximate solution of the optimistic version of a bilevel problem on the basis of the method of directing neighborhoods, the algorithm of finding the solutions for a parametric problem of integer programming of a lower level is proposed. The integer programming problem of a higher level with Boolean variables is solved on the basis of local algorithms.